Comparison of Ga-68 PSMA PET/CT and Multiparametric MRI for Initial Detection and Staging of Prostate Cancer - Gauthaman, Dinesh Kumar; Luthra, Karuna; Lele, Vikram (World Journal of Nuclear Medicine, 2024)
Background Multiparametric magnetic resonance imaging (mpMRI) is widely used for the evaluation of prostate cancer and is known to have better accuracy. Gallium-68 prostate-specific membrane antigen (Ga-68 PSMA) is a radiotracer that shows high localization in prostate cancer cells.Purpose The purpose of this study was to assess the sensitivity and utility of Ga-68 PSMA positron emission tomography/computed tomography (PET/CT) in comparison with mpMRI as a noninvasive imaging technique for the initial diagnosis and locoregional staging of prostate cancer using transrectal ultrasound (TRUS)-guided biopsy as gold standard.Materials and Methods This prospective observational study conducted from August 2017 to April 2020 evaluated 60 men (n = 60) with biopsy-proven prostate carcinoma. They underwent mpMRI and Ga-68 PSMA PET/CT scans within 14 days with TRUS biopsy being gold standard. T staging of disease, N staging of lymph nodes within the pelvis, and M staging of lesions in pelvic bones (within the imaging field of mpMRI) were compared using PSPP version 1.0.1 statistical software.Results All 60 men with a mean age of 69.9 ± 9.35 years showed Ga-68 PSMA avid disease, whereas 55 were detected by mpMRI. The sensitivity in detection of prostate lesions (with 95% confidence interval) was 99.08% for Ga-68 PSMA PET/CT and 84.40% for mpMRI. Ga-68 PSMA PET/CT detected greater number of patients with regional lymph nodal involvement (19/60) as compared with mpMRI (12/60). Ga-68 PSMA PET/CT showed PSMA avid pelvic skeletal lesions in nine patients, whereas mpMRI detected pelvic lesions in six patients. In addition, four other patients showed extrapelvic skeletal lesions on Ga-68 PSMA PET/CT.Conclusion Ga-68 PSMA PET/CT has superior sensitivity in detection of primary prostate tumor, as compared with mpMRI. Both modalities correlate well in detection of seminal vesicle involvement. Ga-68 PSMA PET/CT outperformed mpMRI in detection of lymph nodal and skeletal metastases. Hence, Ga-68 PSMA PET/CT should be considered as first-line diagnostic modality for carcinoma prostate.Summary Statement: Ga-68 PSMA PET/CT shows superior diagnostic performance than mpMRI in the evaluation of prostate cancer.
Keywords: prostate cancer; staging; PSMA PET/CT; multiparametric MRI; noninvasive imaging technique